Universiti Malaysia Sabah’s medical and nursing undergraduate student`s satisfaction towards rural community outreach health promotion posting in Ranau, Sabah - Segaran Ramodran; Billy Bryan Jafrin; Mellonna Ignatia Jeffrey Liew; Nurul MadihahMohd Raeh; Juecella Joyce Jalius (Malaysian Journal of Medicine and Health Sciences, 2020)
EC1773 is a community outreach program conducted annually by Universiti Malaysia Sabah (UMS). It serves as a platform for nursing and medical students to collaborate hands-on health promotion for rural communities. As of date, there has been no empirical study to gauge student`s post-program satisfaction. This study aims to evaluate satisfaction among students who have undergone the UMS-led community out-reach program and identify gaps for improvement. Methods: The study entailed a cross-sectional design involving 165 (N) nursing(n=65) and medical students (n=100) who had completed a 10-day rural outreach program. Ethical approval was obtained from the Research Ethics Committee of UMS as well-informed consent from respondents. A 25- item questionnaire requir¬ing Likert-scale responsewas used to evaluatethe level of satisfaction across 5 sub-categories namely; pre-departure preparation & briefing;onsite facilities and logistics; teamwork; community participation and learning achievements. Results: Among 165 nursing -medical students in the study, 88% (n=146) were satisfied and 12% (n=19) were dis¬satisfied with the UMS-led outreach program. Sub-category items rated as satisfactory were community participation 96% and learning achievements 91%. Poor satisfaction highlighted by respondents regarding the out-reach program were inadequacy of facilities and poor logistics 62% and quality of pre-departure preparation and briefing 66%. Nursing students reported significantly higher dissatisfaction (p=0.04) regarding teamwork and adequacy of onsite facilities and logistics. Conclusion: Findings from this study infers that student’s post-evaluation towards the UMS-led outreach is generally satisfactory but has specific shortfalls that need to be addressed.